The Effect of Class Repetition on the Academic Performance of Pupils in Lower Primary Schools in Homa-Bay Sub-County - Aduda, Philip Otieno; Kodero, Hesborn M. N.; Sichari, Manson (International Journal For Research In Educational Studies, 2019)
Class repetition is used as a strategy of improving academic performance in schools in Kenya. The study objective was to examine the effect of class repetition on pupil’s academic performance in public lower primary schools in Homa-Bay Sub-county. The study employed descriptive survey design and document analysis. The analysis of data was done using descriptive statistics as well inferential statistics using Statistical Package for Social Sciences (SPSS). The target population entailed all the class three repeaters in the 67 public primary schools in Homa-Bay Sub-County. Head teachers and class three teachers also took part in the study as informants. To obtain the desired number of schools out of the 67 public primary schools in Homa-Bay Sub-County from which the researcher obtained the respondents, the Krejcie and Morgan Sample Size Table (1970) was used. Simple random sampling was adopted in selecting 30 schools to include in the sample. In these 30 schools, there were a total of 42 class three repeaters all of them were involved in the study through the whole population purposive sampling. The study found that class repetition has a positive effect on the academic performance of lower primary pupils in that pupils perform better after repeating a class as indicated by a paired sample statistics which showed that on repeating a class, the pupils’ academic performance (m=263.38, sd=128.92) was higher than their mean academic performance before repeating (=178.07, sd=68.55).This difference in the mean scores is statistically significant, t(41)=4.949, t<0.001. It was further noted that more than half of the respondents(headteacher and class teachers) (80%) agreed that class repetition indeed has a positive effect on academic improvement, compared to only 20% of the respondents who stated that there is no effect on academic improvement after repetition. The researcher recommends that the Ministry of Education should review the policy that outlaws class repetition and allow teachers, parents and other educational stakeholders to consultatively make decisions on whether a pupil should repeat a class or not. The researcher suggests that a study should be carried out on the impact of ‘no repetition’ policy on children’s behaviour and academic performance.